Policy, People, and the New Professional De-professionalisation and Re-professionalisation in Care and Welfare - Duyvendak, Jan Willem; Knijn, Trudie; Kremer, Monique; Duyvendak, Jan Willem; Knijn, Trudie; Kremer, Monique (Amsterdam University Press, 2006)
Engaging with the acclaimed American sociologist Eliot Freidson's argument about professionalism's 'third logic' (a viable alternative to bureaucracy and consumerism), Dutch, British, French and German contributors to this volume bring together three political and academic debates rarely tackled jointly: professionalism, change, and policy, in the context of the increasing marketization and bureaucratization of healthcare and welfare. As attempts to cope with Europe's increasingly ageing and multicultural societies are being implemented, this first title in a uniquely positioned series provides an exhaustive analysis of the road travelled so far. This title is available in the OAPEN Library - http://www.oapen.org.
English
Keywords: Medicine: general issues; Comparative politics; Sociology; Political Science; Health Sciences; Sociology